Demonstrators holding signs - Ted Sahl (photographer):::Creator::::::::::::
Photograph shows two men demonstrating on a street. One man is carrying a bullhorn and a banner that reads "The wages of sin is death. Romans 6:23" The words are configured so that the letter A from wages, I from sin, D from death and S from Romans are in alignment vertically. Those letters are also in a different color so that the word "AIDS" is clearly visible. The second man is carrying a sign that reads "God loves me just as I am!"